A Comparative Study of the Biodurability and Persistence of Gold, Silver and Titanium Dioxide Nanoparticles Using the Continuous Flow through System - Odwa Mbanga; Ewa Cukrowska; Mary Gulumian (Nanomaterials, 2023)
The potential for nanoparticles to cause harm to human health and the environment is correlated with their biodurability in the human body and persistence in the environment. Dissolution testing serves to predict biodurability and nanoparticle environmental persistence. In this study, dissolution testing using the continuous flow through system was used to investigate the biodurability and persistence of gold nanoparticles (AuNPs), silver nanoparticles (AgNPs) and titanium dioxide nanoparticles (TiO2 NPs) in five different simulated biological fluids and two synthetic environmental media to predict their behaviour in real life situations. This study examined the physicochemical properties and agglomeration state of gold, silver and titanium dioxide nanoparticles before and after dissolution tests using three different techniques (UV-vis, XRD and TEM). The UV-vis spectra revealed that all three nanoparticles shifted to higher wavelengths after being exposed to simulated fluids. The titanium powder was found to be mixed with both rutile and anatase, according to XRD examination. The average diameter of gold nanoparticles was 14 nm, silver nanoparticles were 10 nm and titanium dioxide nanoparticles were 25 nm, according to TEM images. The gold and silver nanoparticles were observed to be spherical, but the titanium dioxide nanoparticles were irregular in shape, with some being spherical. The level of dissolved nanoparticles in simulated acidic media was higher in magnitude compared to that dissolved in simulated alkaline media. The results obtained via the continuous flow through dissolution system also displayed very significant dissolution rates. For TiO2 NPs the calculated half-times were in the range of 13–14 days, followed by AuNPs ranging between 4–12 days, significantly longer if compared to the half-times of AgNPs ranging between 2–7 days. AuNPs and TiO2 NPs were characterized by low dissolution rates therefore are expected to be (bio)durable in physiological surroundings and persistent in the environment thus, they might impose long-term effects on humans and the environment. In contrast, AgNPs have high dissolution rates and not (bio)durable and hence may cause short-term effects. The results suggest a hierarchy of biodurability and persistence of TiO2 NPs > AuNPs > AgNPs. It is recommended that nanoparticle product developers should follow the test guidelines stipulated by the OECD to ensure product safety for use before it is taken to the market.